Effect of basic fibroblast growth factor in mouse embryonic stem cell culture and osteogenic differentiation. (4th June 2012) - Rose, Laura C.; Fitzsimmons, Ross; Lee, Poh; Krawetz, Roman; Rancourt, Derrick E.; Uludağ, Hasan
Abstract Embryonic stem cells are actively explored as a cell source in tissue engineering and regenerative medicine involving bone repair. Basic fibroblast growth factor (bFGF) has been a valuable growth factor to support the culture of human stem cells as well as their osteogenic differentiation, but the influence of bFGF on mouse embryonic stem (mES) cells is not known. Towards this goal, D3 cells were treated with bFGF during maintenance conditions and during spontaneous and osteogenic differentiation. In feeder‐free monolayers, up to 40 ng/ml of exogenous bFGF did not support self‐renewal of mES without LIF during cell expansion. During spontaneous differentiation in high‐density cultures, bFGF stimulated cell proliferation under certain conditions but did not influence differentiation, as judged by stage‐specific embryonic antigen‐1 expression. The addition of bFGF reduced the alkaline phosphatase (ALP) activity associated with osteoblast activity during differentiation induced by osteogenic supplements, although the extent of mineralization was unaffected by bFGF. The bFGF increased the mesenchymal stem cell marker Sca‐1 in an mES cell population and led to an enhanced increase in osteocalcin and runx2 expression in combination with BMP‐2. These results suggest that bFGF could be utilized to expand the cell population in high‐density cultures in addition to enriching the BMP‐2 responsiveness of mES cells. Copyright © 2012 John Wiley & Sons, Ltd.